Pemberdayaan Kader Kesehatan Remaja untuk Meningkatkan Partisipasi dalam Posyandu Remaja di Kabupaten Sigi, Sulawesi Tengah - Taqwin Taqwin; Narmin Narmin; Sri Restu Tempali; Nasrul Nasrul (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Adolescent health services remain a concern in Central Sulawesi due to low adolescent participation in adolescent posyandu (community health posts for adolescents). This community service activity aims to empower youth health cadres to increase participation in the implementation of youth health posts in Tanambulawa Subdistrict, Sigi Regency, Central Sulawesi. The intervention comprised training and the implementation of adolescent posyandu. Evaluation employed a pretest–posttest design for the cadres and monitoring of posyandu activities. The program was conducted in February–March 2024. Twenty-five cadres participated in the training, and 17 adolescents attended the posyandu. The average knowledge score increased from 6.04 (pretest) to 8.32 (posttest). The adolescent posyandu was held on 8 March 2024 in Sibalaya Selatan Village. In conclusion, the training improved cadres’ knowledge about adolescent posyandu and adolescent anemia, and the posyandu activities were successfully implemented. It is recommended that adolescent program coordinators and cadres intensify outreach to adolescents and parents regarding the importance of adolescent posyandu.